Hukum MLM dalam pandangan syariah - gazali, gazali gazali (FAI Unismuh Palu, 2018)
This study aims to provide a general explanation of Islamic views of multilevel marketing (MLM). This research will make it easier for us to identify each type of multilevel marketing that established in a company. Because the concept of multilevel marketing that applied in every company is not same one to another, then, in the discussion of it can not be generalized to all multilevel marketing companies, but is to identify the certain points that applied in the it system. This research is a library-based research, conducted through the study of literatures that discuss about the economic theories, multilevel marketing and also the classical and contemporary book of fiqh.